Assessment of bacteriological quality of drinking water from various sources in Amritsar district of northern India - Malhotra, Sita; Sidhu, Shailpreet K; Devi, Pushpa (The Journal of Infection in Developing Countries, 2015)
Introduction: Safe water is a precondition for health and development and is a basic human right, yet it is still denied to hundreds of millions of people throughout the developing world. Water-related diseases caused by insufficient safe water supplies, coupled with poor sanitation and hygiene, cause 3.4 million deaths a year, mostly in children. Methodology: The present study was conducted on 1,317 drinking water samples from various water sources in Amritsar district in northern India. All the samples were analyzed to assess bacteriological quality of water for presumptive coliform count by the multiple tube test. Results: A total of 42.9% (565/1,317) samples from various sources were found to be unfit for human consumption. Of the total 565 unsatisfactory samples, 253 were from submersible pumps, 197 were from taps of piped supply (domestic/public), 79 were from hand pumps, and 36 were from various other sources A significantly high level of contamination was observed in samples collected from submersible pumps (47.6%) and water tanks (47.3%), as these sources of water are more exposed and liable to contamination. Conclusions: Despite continuous efforts by the government, civil society, and the international community, over a billion people still do not have access to improved water resources. Bacteriological assessment of all sources of drinking should be planned and conducted on regular basis to prevent waterborne dissemination of diseases.